Void in Law: Criminal Regulation Vacuum on the Detrimental Impact of AI Artificial Intelligence - Hendri Khuan (Journal of Strafvordering Indonesian, 2025)
Advances in artificial intelligence (AI) technology have brought new challenges in the realm of criminal law, especially related to accountability for autonomous actions that cause legal losses. Indonesia's criminal law system, which is still based on an anthropo-centric paradigm with the conditions of actus reus and mens rea, has not been able to accommodate non-human digital entities such as AI. The absence of explicit criminal norms against AI's detrimental behavior leads to a legal void, where real harm cannot be effectively acted upon. Law Number 11 of 2008 concerning Information and Electronic Transactions (ITE Law) has not specifically regulated the attribution of errors to AI, developers, and system operators. This study uses normative juridical methods with conceptual and comparative legal approaches to analyze the need for the formation of a new criminal framework for AI. The results of the study show the urgency of reformulating criminal regulations that are risk-based and adaptive to technological developments, as reflected in the EU Artificial Intelligence Act model. It is also necessary to strengthen the concept of indirect criminal liability and the possibility of recognition of electronic legal entities. Without regulatory innovation, Indonesia's criminal justice system risks failing to protect the digital society fairly and effectively. This study recommends the establishment of specific norms that are responsive to the risks of AI technology